Floral Concept of ‘Voroniache Oko’ (Raven’s Eye) in Folklore Texts from the Western Polissia: a Linguo-Cultural Aspect (Linguostylistic Studies, 2025)
Botanical vocabulary belongs to the archaic language layer and is an integral part of linguistic culture. It reflects people's life experience and the results of their observations of the world around, therefore the names of plants provide for establishing specific features of the cultural traditions of the people. Plant names with zoonymic components constitute a separate thematic group within the botanical vocabulary. The plant names with zoonymic components constitute a separate thematic group within the botanical vocabulary. Phytonominations often become the object of linguistic and cultural research. This approach makes it possible to consider the ways of representing culture in language and to find out the peculiarities of the people's worldview. The main tool for conducting linguo-cultural analysis is the concept of cultural connotation. The essence of floronomena with a zoonym component is associations based on external similarity and similarity of functions of animals and plants. The object of the study is the cultural connotations of the phytonomen voroniache oko in folklore texts from Western Polissia. The most frequent motivational feature is the poisonousness of the plant. Thus, the designation voroniache indicates the toxic effect of this plant on humans and animals. Also, it adds an emotional aspect to the assessment of the poisonousness of the plant, which warns a person about the danger. Another motivational feature is the place of growth of the plant (the ornithonym component voron (raven)is present in the names of forest and moisture-loving plants). The phenomenon of phytonymic opposition reflects popular ideas about mimicry in the plant world. The phytonomen voroniache oko implies additional pejorative semantics and forms an opposition to the names of useful plants. Folklore texts in which the nomen voroniache oko (raven’s eye) occurs reflect the negative attitude of native speakers towards the raven and explain the poisonousness of this plant.Linguistic and cultural studies of botanical vocabulary allow us to establish unique and universal features inherent in both plants and animals in the folk worldview of the Western Polissia inhabitants.
Keywords: flora concept; linguoculturology; cultural connotation; folklore